A CASE OF PROLACTIN AND GROWTH HORMONE CO-SECRETING PITUITARY MACROADENOMA - Kannesan, Dineash Kumar; Lian, Zi Yang; Hussein, Zanariah (Journal of the ASEAN Federation of Endocrine Societies, 2025)
INTRODUCTION/BACKGROUND Prolactin (PRL) and growth hormone (GH) co-secreting pituitary macroadenomas are relatively rare and exhibit a multifaceted clinical presentation. Optimal management of PRL/GH co-secreting pituitary adenomas remains clinically challenging. We report a case of a PRL/GH co-secreting pituitary macroadenoma managed with cabergoline monotherapy. CASE A 25-year-old male without comorbidities presented with a chronic headache for eight years. Pituitary MRI revealed a pituitary macroadenoma measuring 1.7 x 2.5 x 1.8 cm compressing the optic chiasm, with minimal extension into the right cavernous sinus and mild sellar widening. He had markedly elevated prolactin at 11,170 mIU/L and was started on Cabergoline 0.25 mg twice weekly and transferred care to our centre for further management of functioning pituitary macroadenoma. Notable physical examination findings included frontal bossing and prognathism, but no macroglossia, skin tags, or tremors were seen. A visual field assessment revealed no defects. Hormonal workup exhibited elevated GH of 4.75 µg/L (5x the upper limit of normal), IGF-1 of 418.9 ng/mL, prolactin of 3,433 mIU/mL and failure of GH suppression on OGTT, consistent with a GH and prolactin-secreting pituitary adenoma. The multidisciplinary team reached a consensus that curative surgery is not feasible due to tumor extension into the right cavernous sinus. They recommended increasing his Cabergoline dosage to 3-4 mg weekly. The patient remains asymptomatic and his prolactin level is 784 mIU/mL while on Cabergoline 3.5 mg weekly. A follow-up MRI shows a smaller pituitary lesion with resolution of the optic chiasm mass effect. Currently, the patient is not inclined to consider surgery. CONCLUSION Surgical intervention is typically the first-line treatment for mixed co-secreting pituitary adenomas. However, cabergoline is known to effectively normalize prolactin levels in patients with hyperprolactinemia caused by mixed adenomas. In this particular case, cabergoline monotherapy appears to be successful at controlling both tumor growth and prolactin levels.